The factors wich relate to the quality of river Batang Ayumi in Kantin on Nort Padangsidimpuan, Padangsidimpuan 2013 - dian akhfiana fitri; wirsal hasan; indra chahaya (Lingkungan dan Kesehatan Kerja, 2014)
Batang Ayumi River is a river that flows through the Padangsidimpuan city. In Kantin Village are people living on the banks / river banks. This has the potential to affect the water quality of the river Batang Ayumi caused domestic waste (BPS, 2008). The research aims to study the behavior (knowledge, attitude, practice), the culture and the role of community leaders the Kantin village regarding respondent characteristics, Rod Ayumi river water quality before and after passing through the village canteen (BOD, COD, DO, Detergent, TSS, total Coliform and Colifecal) and relations between them. Types of analytic study with cross-sectional study design. Respondents are mothers who live right on the edge of the river Batang Ayumi numbered 64 people and the quality of the river water upstream and downstream in the Kantin Village. The results, there is a relationship between behavior, culture and assessment TOMA of water quality Batang Ayumi which chemical parameters (BOD, COD, DO, Detergents), physics parameter (TSS), microbiological parameters (total coliform and Colifecal). The behavioral significance of the parameter values ​​chemistry, physics and microbiology is p = 0.003 (P <0.05), the culture with chemistry parameter, physics parameter, and microbiology parameter is p = 0.016 (P <0.05), with an assessment of the parameters TOMA chemistry parameter, physics parameter, and microbiology parameter is p = 0.002 (p <0.05). For government and community leaders is recommended to keep water quality of Batang Ayumi river by providing information through counseling and strict rules about building permits. For society is expected to care and comply the regulations of water-quality.